Pathologist variation in reporting cervical borderline epithelial abnormalities and cervical intraepithelial neoplasia. Issue 1 (January 1995) - Creagh, T; Bridger, J E; Kupek, E; Fish, D E; Martin-Bates, E; Wilkins, M J
Abstract : AIMS–To evaluate the interobserver variation in the diagnosis of cervical intraepithelial lesions, including the new category "borderline abnormalities of uncertain significance" (BAUS) which has not been tested before. METHODS–Biopsy specimens of 122 patients were reviewed by five histopathologists and the diagnoses subjected to kappa statistical analysis. RESULTS–There was poor interobserver agreement in all categories, particularly between BAUS and normal tissue. CONCLUSIONS–The current guidelines for the histological diagnosis of cervical intraepithelial neoplasia and BAUS are poorly reproducible.